ANALISIS KESIAPAN GURU DALAM MENGIMPLEMENTASIKAN PEMBELAJARAN MENDALAM TERINTEGRASI STEAM - Ernilawati, Ernilawati; Wardhani, Sri; Genisa, Marlina Ummas; Astriani, Meli (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Deep learning integrated with the STEAM approach is a learning paradigm that emphasizes conceptual understanding, critical thinking skills, creativity, and the application of knowledge in real-life contexts. The successful implementation of this approach is highly dependent on teacher readiness, including conceptual understanding, pedagogical competence, and the availability of supporting facilities. This study aims to analyze the readiness of teachers at SMPN 2 Babat Supat in implementing deep learning integrated with STEAM and to identify the supporting and inhibiting factors in its implementation. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, classroom observations, and documentation involving subject teachers and the school principal. Data analysis was conducted through data reduction, data display, and conclusion drawing, supported by source triangulation. The findings indicate that teachers generally possess a basic understanding of deep learning and the STEAM approach and demonstrate pedagogical readiness in designing student-centered learning activities that encourage active participation. Teachers have also utilized various learning media, including digital platforms, to support the learning process. However, the implementation of deep learning integrated with STEAM has not been fully optimal due to several constraints, particularly limited and unstable internet connectivity, insufficient continuous professional training, and limited supporting facilities. These findings highlight the need for policy support, improvement of infrastructure, and sustainable professional development programs to strengthen teacher readiness and ensure the effective implementation of deep learning integrated with STEAM. ABSTRAK Pembelajaran mendalam terintegrasi STEAM merupakan pendekatan pembelajaran yang menekankan pemahaman konseptual, keterampilan berpikir kritis, kreativitas, serta keterkaitan pembelajaran dengan konteks kehidupan nyata. Keberhasilan implementasi pendekatan ini sangat bergantung pada kesiapan guru, baik dari aspek pemahaman konseptual, kompetensi pedagogik, maupun dukungan sarana pembelajaran. Penelitian ini bertujuan untuk menganalisis kesiapan guru SMPN 2 Babat Supat dalam mengimplementasikan pembelajaran mendalam terintegrasi STEAM serta mengidentifikasi faktor pendukung dan penghambat pelaksanaannya. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa wawancara mendalam, observasi pembelajaran, dan dokumentasi. Subjek penelitian terdiri atas guru mata pelajaran dan kepala sekolah. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan, serta diperkuat dengan triangulasi sumber. Hasil penelitian menunjukkan bahwa guru pada umumnya telah memahami konsep dasar pembelajaran mendalam dan STEAM serta menunjukkan kesiapan pedagogik dalam merancang pembelajaran yang mendorong keterlibatan aktif siswa. Guru juga memanfaatkan berbagai media pembelajaran, termasuk media digital, untuk mendukung proses pembelajaran. Namun demikian, implementasi pembelajaran mendalam terintegrasi STEAM belum berjalan optimal karena masih dihadapkan pada kendala, terutama keterbatasan akses dan kestabilan sinyal internet, minimnya pelatihan berkelanjutan, serta keterbatasan fasilitas pendukung. Temuan ini menunjukkan perlunya dukungan kebijakan, peningkatan sarana prasarana, dan program pengembangan profesional guru yang berkelanjutan guna mendukung implementasi pembelajaran mendalam terintegrasi STEAM secara efektif.